Spatial aromatic fences of metal–organic frameworks for manipulating the electron spin of a fulleropyrrolidine nitroxide radical. Issue 28 (30th June 2016) - Cao, Jiamei; Feng, Yongqiang; Zhou, Shengju; Sun, Xiaofeng; Wang, Taishan; Wang, Chunru; Li, Hongguang
Abstract : The effect of two typical metal–organic frameworks (MOF-177 and MIL-53) with a distinctive aperture size and spatial geometry on the electron spin properties of a spin-labeled fullerene was investigated. Abstract : The electron spin properties of a fulleropyrrolidine nitroxide radical incarcerated in the pores of MOF-177 and MIL-53 respectively were investigated for the first time. It was found that the spatial confinement effect and intramolecular interactions in these two solid-state spin systems lead to dramatically distinctive spin dynamics.